2021
DOI: 10.1088/1755-1315/945/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Carbon Dioxide Concentration on Residents in the Area of a Cement Plant in Perak, Malaysia

Abstract: Nowadays, concrete is used extensively in construction. The cement factory must generate massive amounts of cement each year in order to deliver enough concrete. Carbon dioxide emitted during the cement manufacturing and raw materials transportation processes contributes to air pollution and greenhouse gas emissions, deteriorating air and water quality and posing health risks to residents. Hence, the purpose of this research is to investigate the effects of carbon dioxide absorption on local residents and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Numerous studies have suggested that lower carbon dioxide (CO2) emissions indicate better environmental quality. The IPCC report recommends reducing greenhouse gas emissions, particularly CO2, by 50-80% by 2050 (Rau et al, 2021). Therefore, a clear understanding of how to curb CO2 emissions is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have suggested that lower carbon dioxide (CO2) emissions indicate better environmental quality. The IPCC report recommends reducing greenhouse gas emissions, particularly CO2, by 50-80% by 2050 (Rau et al, 2021). Therefore, a clear understanding of how to curb CO2 emissions is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Malaysia, the construction sector is of great importance and has seen significant growth in recent years [44,45]. Similarly, the regulations governing the construction industry in this country promote sustainable and environmentally friendly construction [46,47].…”
Section: Publications By Countrymentioning
confidence: 99%
“…Cement has negative effect on global warming and generates carbon footprint [1][2][3]. Hence, partial substitution material is needed.…”
Section: Introductionmentioning
confidence: 99%